Neuroprotection of Neuro2a cells and the cytokine suppressive and anti-inflammatory mode of action of resveratrol in activated RAW264.7 macrophages and C8–B4 microglia. (May 2016) - Steiner, Nicole; Balez, Rachelle; Karunaweera, Niloo; Lind, Joanne M.; Münch, Gerald; Ooi, Lezanne
Abstract: Chronic inflammation is a hallmark of neurodegenerative disease and cytotoxic levels of nitric oxide (NO) and pro-inflammatory cytokines can initiate neuronal death pathways. A range of cellular assays were used to assess the anti-inflammatory and neuroprotective action of resveratrol using murine microglial (C8–B4), macrophage (RAW264.7) and neuronal-like (Neuro2a) cell lines. We examined the release of NO by Griess assay and used a Bioplex array to measure a panel of pro- and anti-inflammatory cytokines and chemokines, in response to the inflammatory stimuli lipopolysaccharide (LPS) and interferon-γ (IFN-γ). Resveratrol was a potent inhibitor of NO and cytokine release in activated macrophages and microglia. The activity of resveratrol increased marginally in potency with longer pre-incubation times in cell culture that was not due to cytotoxicity. Using an NO donor we show that resveratrol can protect Neuro2a cells from cytotoxic concentrations of NO. The protective effect of resveratrol from pro-inflammatory signalling in RAW264.7 cells was confirmed in co-culture experiments leading to increased survival of Neuro2a cells. Together our data are indicative of the potential neuroprotective effect of resveratrol during nitrosative stress and neuroinflammation.